Pengaruh Motivasi dan Lingkungan Kerja terhadap Semangat Kerja Karyawan : Survei pada Karyawan RM. Hj Ocoh Tasikmalaya - Rena Kuspita Sari; Rita Tri Yusnita; Arga Sutrisna (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine and analyze the effect of motivation and work environment on employee spirit (a survey of employees at RM. Hj Ocoh Jl. Mangin and RM. Hj Ocoh Jl. Sutisna Senjaya Tasikmalaya). The method used in this study is causality through a census approach. With a research sample of 60 employees of PT. Independent Power of Grace. The data used is primary data. The analytical tool used in this research is Path Analysis using SPSS 26.0. The results showed that Motivation has a very good rating classification, the Work Environment has a very good rating classification and Work Spirit has a good rating classification for RM Employees. Hj Ocoh. Simultaneously, motivation and work environment have a significant effect on employee spirit at RM. Hj Ocoh. Partially, motivation and work environment have a significant effect on employee spirit at RM. Hj Ocoh.. Hj Ocoh. Work Environment has an effect on Employee spirit through Motivation for RM Employees. Hj Ocoh.